THE NATURAL HABITAT OF BEGONIA ON THE ISLAND OF BALI: MICROCLIMATE PREFERENCE IN TWO FOREST SITES IN BEDUGUL - Annisa Satyanti (BIOTROPIA, 2012)
A study on Begonia’s ecology was conducted in two forest sites, a nature reserve and reboisation forest, respectively, in Bedugul Bali. The objective of the study was to describe Begonia species found in respective forest sites, to gather information on abiotic factors and to find the influences of these abiotic factors to the abundance of Begonia species. Three species were identified as B. multangula, B. baliensis and B. longifolia. There were two form of B. longifolia, white and red. The multivariate analysis (PCA) showed that abiotic factors measured were relatively similar among plots. In addition, no particular abiotic factor, from multivariate analysis, showed specific influence on Begonia species frequency. Interestingly, the multivariate analysis also implied that B. latifolia has different microclimate preference between forms (white and red). The abundance, refers to the frequency, of all of species in two forests was similar (t-test, p=0.061). Pooling the data from the fourty plots (two forest sites) and white and red forms of B. longifolia together, B. multangula and B. longifolia found were similarly abundant between species (t- test, p=0.460).